Techno stress among medical freshmen: An exploratory study - Nirupam Madaan; LaxmiTej Wundavalli; Sujata Satapathy (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Use of technology and ICT tools is ubiquitous among college students including medical students. However overuse or misuse may lead to many physical and psychological problems including the risk of harming professional standing in the long term. The purpose of this study was to explore techno stress among freshmen at a medical institute and to suggest measures to reduce problematic use of technology pertaining to internet. OBJECTIVES: (i) To explore the extent of technology use including internet among medical freshmen, (ii) To identify the content of usage (iii) To quantify the extent of techno stress and iv. To suggest measures to reduce problematic use of technology. MATERIALS AND METHODS: The sample comprised all the freshmen at a medical institute (n = 61). A semi structured questionnaire was used to collect socio demographic details of students and their patterns of technology usage. Perceived Stress Scale was used to measure stress. RESULTS: The mean age of the sample was 18.34 (±0.58) years comprising 68% males and 32% females. Students spent a mean time of 3.96 h/day on the technology tools (standard deviation = 4.99). Ninety-two percent of the students used technology for educational purposes followed by entertainment (89%), social networking (77.78%), watching films (70.37%), communication (66.67%) and watching pornography (46.3%). 11.47% had symptoms suggestive of problematic internet use. One percent had craving suggestive of addiction. All these had stress out of which 43% had high and 57% had moderate levels of stress. DISCUSSION: Considering the students' present usage of social media, it can serve as a potent academic tool. However, awareness is required to be raised with regard to its use as a medical professional. CONCLUSION: Use of technology is crucial in the current academic world and restrictions on usage may neither be practical nor feasible. However, understanding patterns of usage among students is a preliminary step that can enable educators and administrators to formulate guidelines to channelise their usage in more productive ways.